2018
DOI: 10.1021/acs.jpclett.8b02130
|View full text |Cite
|
Sign up to set email alerts
|

Unique Energy Transfer in Fluorescein-Conjugated Au22 Nanoclusters Leading to 160-Fold pH-Contrasting Photoluminescence

Abstract: Accurate measurements of intracellular pH are of crucial importance in understanding the cellular activities and in the development of intracellular drug delivery systems. Here we report a highly sensitive pH probe based on a fluorescein-conjugated Au nanocluster. Steady-state photoluminescence (PL) measurements have shown that, when conjugated to Au, fluorescein exhibits more than 160-fold pH-contrasting PL in the pH range of 4.3-7.8. Transient absorption measurements show that there are two competing ultrafa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…The use of chromophore ligands can control photo-functions of metal nanoparticles and metal NCs. [110][111][112][113] Two-photon absorption of ligand-protected metal NCs shows a nonlinear optical property that is attractive for applications such as biological imaging and PDT. 114 Vangara et al demonstrated twophoton PDT under 860 nm NIR excitation for multiple drug resistance bacteria (MDRB) using a nanocomposite of a-lipoic acid stabilized Au NCs and graphene quantum dots (GQDs) (Au NCs-GQDs nanocomposite), 115 where the GQDs with high NIR absorption act as two-photon donor-chromophores, while the Au NCs act as acceptors.…”
Section: Basic Principle Of Photosensitization For Pdtmentioning
confidence: 99%
“…The use of chromophore ligands can control photo-functions of metal nanoparticles and metal NCs. [110][111][112][113] Two-photon absorption of ligand-protected metal NCs shows a nonlinear optical property that is attractive for applications such as biological imaging and PDT. 114 Vangara et al demonstrated twophoton PDT under 860 nm NIR excitation for multiple drug resistance bacteria (MDRB) using a nanocomposite of a-lipoic acid stabilized Au NCs and graphene quantum dots (GQDs) (Au NCs-GQDs nanocomposite), 115 where the GQDs with high NIR absorption act as two-photon donor-chromophores, while the Au NCs act as acceptors.…”
Section: Basic Principle Of Photosensitization For Pdtmentioning
confidence: 99%
“…However, the slope is definitely smaller when compared to Au 13 nm nanoparticle that was passivated with a surfactant, again signifying the importance of the ligand on electron-phonon relaxation dynamics. 30 Pump energy (nJ) B Figure 5. Electron-phonon relaxation as a function of pump pulse energy for (A) Au279 (TBBT), Au329 (SC2Ph), Au329 (SC6) and Au13 nm (Citrate), (B) Au329 (SC6), Au~1400 (SC6) and Au~2000 (SC6).…”
Section: Ultrafast Transient Absorption Measurementsmentioning
confidence: 99%
“…3,4,14,15,19,[24][25][26]43,44 In recent years, thiolate-protected gold clusters have received enormous research attention as the clusters with sizes less than 2 nm seem to show interesting quantum size behavior and excitonic properties. 27,28,30,31,[45][46][47] The advent of modern synthetic and characterization techniques has made the science of atomically precise thiolate-protected gold clusters interesting for theoreticians and experimentalists. Even thiolate protected gold clusters show plasmonic properties and Au329 protected with hexane thiol was found to be the smallest aliphatic thiolate protected plasmonic Au 4 NPs.…”
Section: Introductionmentioning
confidence: 99%
“…AF was then conjugated to the CBz‐protected gold clusters via a dicyclohexyl carbodiimide/ N ‐hydroxysuccinimide (DCC/NHS) coupling reaction. [ 14 ] ( Figure a, see Experimental Section for details). After removing excess AF and reaction impurities using a 10 kDa desalting column, AF‐conjugated gold clusters were separated by polyacrylamide gel electrophoresis (PAGE).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we showed that ultrafast energy transfer from nonthermalized states of Au 22 cluster to the conjugated aminofluorescein (AF) led to over 160‐fold pH‐contrasting photoluminescence (PL). [ 14 ] This result has stimulated us to investigate the size effect on energy harvesting from nonthermalized excited states of gold clusters of various sizes. In this study, we used femtosecond transient absorption spectroscopy to study energy harvesting from the nonthermalized states of various‐sized gold clusters ranging from Au 18 to Au ≈940 .…”
Section: Introductionmentioning
confidence: 99%